A Survey of MicroRNA Length Variants Contributing to miRNome Complexity in Peach (Prunus Persica L.) - Colaiacovo, Moreno; Bernardo, Letizia; Centomani, Isabella; Crosatti, Cristina; Giusti, Lorenzo; Orrù, Luigi; Tacconi, Gianni; Lamontanara, Antonella; Cattivelli, Luigi; Faccioli, Primetta (Frontiers in Plant Science, 2012)
MicroRNAs (miRNAs) are short non coding RNA molecules produced from hairpin structures and involved in gene expression regulation with major roles in plant development and stress response. Although each annotated miRNA in miRBase (www.mirbase.org) is a single defined sequence with no further details on possible variable sequence length, isomiRs - namely the population of variants of miRNAs coming from the same precursors - have been identified in several species and could represent a way of broadening the regulatory network of the cell. Next-gen-based sequencing makes it possible to comprehensively and accurately assess the entire miRNA repertoire including isomiRs. The aim of this work was to survey the complexity of the peach miRNome by carrying out Illumina high-throughput sequencing of microRNAs in 3 replicates of 5 biological samples arising from a set of different peach organs and/or phenological stages. Three hundred-ninety-two isomiRs (miRNA and miRNA*-related) corresponding to 26 putative miRNA coding loci, have been highlighted by mirDeep-P and analyzed. The presence of the same isomiRs in different biological replicates of a sample and in different tissues demonstrates that the generation of most of the detected isomiRs is not random. The degree of mature sequence heterogeneity is very different for each individual locus. Results obtained in the present work can thus contribute to a deeper view of the miRNome complexity and to better explore the mechanism of action of these tiny regulators.